Representasi Gender Pada Iklan Sajiku Seri Ibu Kuat Sajiku (2025) - Afrilia Mustika Damayanti; Laras Kuntiyasari (Indo Publishing, 2025)
This study aims to uncover the representation of gender bias in the Sajiku Seasoning Flour Advertisement Series